FIGURATIVE LANGUAGE IN THE COLDPLAY ALBUM SELECTED SONG’S - MASLAN M.R. SIHOMBING (JURNAL ILMIAH MAKSITEK, 2021)
This study deals with Figurative language in Coldplay album selected songs. The aims of this study are to find out the kindsof figurative language , to investigate the kinds of figurative language meaning in Coldplay album selected songs. The dataof this research were the lyrics of Coldplay. The research method was descriptive qualitative analysis. It means that thisresearch does not calculate the data and just gives description about figurative language that is contained in Coldplay albumselected songs. The writer obtained all of the data were taken by downloading the lyrics, listening and reading , grouping andchoosing the lyrics that contained the figurative language. From the analysis , ther were five from twelve types of figurativelanguage they were hyperbole, metaphor, irony, simile, and personification. And the contextual meaning from eachexplanation.